Evaluasi Kebijakan Pajak Penghasilan dalam Meningkatkan Penerimaan Negara dan Mendorong Investasi di Indonesia - Davina Dwika; Deswita Saputri; Rudi Sanjaya; M. Raffa Putra; Nailah Hasan (PT. Hasba Edukasi Mandiri, 2026)
Income This study aims to evaluate the effectiveness of Income Tax policy in increasing state revenue and encouraging investment in Indonesia. The research method used is a qualitative approach with a literature review. Research data were obtained from various secondary sources, including scientific journals, reference books, laws and regulations, government reports, and publications from related institutions relevant to taxation policy, state revenue, and investment. Data analysis was conducted using qualitative descriptive analysis techniques through the processes of identification, reduction, classification, interpretation, and synthesis of data. The results of the study indicate that Income Tax policy contributes positively to increasing state revenue through expanding the tax base, improving taxpayer compliance, and modernizing digital-based tax administration. In addition, various tax incentives such as tax holidays, tax allowances, and reduced Income Tax rates can increase investment attractiveness by reducing the cost burden borne by business actors. However, the effectiveness of these policies still faces several challenges, including suboptimal levels of taxpayer compliance, high levels of informal sector activity, tax avoidance practices, and the complexity of tax incentive regulations. The research findings also indicate that the success of tax policies in encouraging investment is not only determined by tax factors, but is also influenced by economic stability, legal certainty, infrastructure quality, and ease of doing business. This study concludes that Indonesia's Income Tax policy has had a positive impact on increasing state revenue and investment growth. Therefore, ongoing policy evaluation and refinement are necessary to create a balance between optimizing state revenue and increasing investment competitiveness to support sustainable national economic development.